Aplikasi Pupuk Organik yang Diperkaya dengan Pupuk Hayati pada Pertumbuhan dan Produksi Jagung di Lahan Pasang Surut - Iin Siti Aminah; Yopie Moelyohadi; Rosmiah Rosmiah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Aminah IS, Moelyadi Y, Rosmiah R. 2019. Application of organic fertilizer enhanced with bio fertilizer in growth and production of maize in tidal swamp. In: Herlinda S et al. (Eds), Prosiding Nasiobal lahan Suboptimal 2-019, Palembang 4–5 September 2019. pp 330-337. Palembang: Unsri Press. Organic fertilizers have the ability to increase soil fertility both physically, chemically and biologically, on the other hand the content of organic matter is not enough to meet nutrient requirements for plants, so it is necessary to add biological fertilizers containing bacteria that can help provide nutrients. This study aims to determine the types of organic fertilizers enriched with biological fertilizers with different concentrations in corn plants (Zea mays L.) in tidal land. This research has been carried out on the ground of farmers in Purwosari Village, Tanjung Lago Subdistrict, Banyuasin Regency, South Sumatra Province held from May to August 2018. The research method uses Split Plot Design with 12 treatment combinations and 3 replications. The treatments are as follows: Organic fertilizer (K), K1=chicken manure compost, K2=Cow compost, K3=Rice Straw Compost, and Biological Fertilizer Dosage, H0=No Biofertilizer, H1= 10ml/litter, H2= 15 ml/litter, H3=20 ml/litter. The variables observed in this study were plant height (cm), number of leaves (strands), leaf area (cm), root length (cm) and dry weight of plants (g). The results showed that the combination of the treatment of chicken manure compost and 20 ml/liter biofertilizer doses gave the highest yield with an average yield of 5.58 kg/plot or equivalent to 7.3 tons/ha of corn shelling.Keywords: biological fertilizer, corn, organic fertilizer